2013
DOI: 10.4102/jef.v6i2.260
|View full text |Cite
|
Sign up to set email alerts
|

Addressing the small business tax compliance burden: Evidence from South Africa

Abstract: Small businesses have the potential to grow the economy, generate jobs and reduce poverty, but they face many constraints including high tax compliance costs and burdens. A comparison of the findings and recommendations made in small business tax compliance cost studies conducted in South Africa with initiatives introduced by the South African Revenue Service (SARS), substantiated by consultations with a SARS and a South African Institute of Chartered Accountants official, reveals that SARS has, in most cases,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 2 publications
0
6
0
Order By: Relevance
“…Because of this scarcity of tax compliance studies in developing countries (for exceptions, see Abdul-Razak & Adafula, 2013;Alabede, Ariffin, & Idris, 2011;Gobena & van Dijke, 2016;Smulders & Naidoo, 2013), there is virtually no comparison of results across cultures. Yet, as noted, the tax environment in many developing countries differs in important ways from that in JUSTICE, TAXPAYERS' IDENTITY, AND TAX COMPLIANCE 25 Europe and the US, as in developing countries (more than in developed nations), taxpayers usually do not view paying taxes as a contribution to the buildup and maintenance of common public goods (Asaminew, 2010;Fjeldstad & Semboja, 2001;Gangl, Torgler, Kirchler, & Hofmann, 2014).…”
Section: Theoretical Implicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Because of this scarcity of tax compliance studies in developing countries (for exceptions, see Abdul-Razak & Adafula, 2013;Alabede, Ariffin, & Idris, 2011;Gobena & van Dijke, 2016;Smulders & Naidoo, 2013), there is virtually no comparison of results across cultures. Yet, as noted, the tax environment in many developing countries differs in important ways from that in JUSTICE, TAXPAYERS' IDENTITY, AND TAX COMPLIANCE 25 Europe and the US, as in developing countries (more than in developed nations), taxpayers usually do not view paying taxes as a contribution to the buildup and maintenance of common public goods (Asaminew, 2010;Fjeldstad & Semboja, 2001;Gangl, Torgler, Kirchler, & Hofmann, 2014).…”
Section: Theoretical Implicationsmentioning
confidence: 99%
“…Third, virtually all studies so far on the relationship between procedural justice and tax compliance have been conducted in developed nations in Europe, Australia, and the US (see Gobena & van Dijke, 2016 for an exception). This reflects the more general trend in the tax compliance literature that almost all research addressing antecedents of tax compliance has been conducted in developed nations (see Doyle, Gallery, Coyle, & Commissioners, 2009;Palil, 2010, for reviews; for exceptions, see Abdul-Razak & Adafula, 2013;Smulders & Naidoo, 2013). This is problematic because the tax environment in developing countries differs strongly from that in developed countries.…”
Section: Introductionmentioning
confidence: 96%
“…In Nigeria, Vincent (2021) observed that enforcement instruments, including the agency costs and the punishment function, are also determinants of tax compliance, although these variables are rarely available for empirical studies. In South Africa, Smulders and Naidoo (2013) found that agency notices significantly affect tax compliance, but they found no significant deterrent effect. In Ghana, Ernest, Danie, and Nicholas (2022), based on studies of data generated from the Internal Revenue Service's Taxpayers Compliance Management Programme (TCMP), observed that due to the low probability of detection, even the threat of agency notices had no observable impact on the level of compliance.…”
Section: Empirical Reviewmentioning
confidence: 96%
“…Institutional regulations are another obstacle to SME development, as these regulations are flexible and change over time in South Africa (Eze and Lose 2023). In support of this affirmation, Smulders and Naidoo (2013) also asserted that businesses are encumbered by the burden of compliance with government regulations in the form of byelaws and sometimes payments of dues and fines. Moreover, SMEs sometimes encounter excessive costs in the form of licensing and registration requirements, which add up to the start-up cost of a business (Kamara 2017).…”
Section: Failure Of Agri-preneurship Businessesmentioning
confidence: 99%